A Sequential Approach in Treatment of Endo-Perio Lesion A Case Report - Sharanappa Kambale; Nagaveni Aspalli; Anil Munavalli; Nishant Ajgaonkar; Roopa Babannavar (Journal of Clinical and Diagnostic Research, 2014)
Endo-perio lesions primarily occur by way of the intimate anatomic and vascular connections between the pulp and the periodontium. Endodontic-periodontal combined lesion is a clinical dilemma because making a differential diagnosis and deciding a prognosis are difficult. An untreated primary endodontic lesion may become secondarily involved with periodontal breakdown, which clinically present unusual signs and symptoms. This may delay the diagnosis and hence the correct treatment. This case report describes diagnosis and treatment protocol for an endo-perio lesion of primary endodontic with secondary periodontal involvement.